The Best I Can Be: How Self‐Accountability Impacts Product Choice in Technology‐Mediated Environments. Issue 5 (May 2017) - Rowe, Zoe O.; Wilson, Hugh N.; Dimitriu, Radu M.; Breiter, Katja; Charnley, Fiona J.
ABSTRACT: Technology‐mediated environments are important not only as the location for an increasing proportion of purchases, but also as an even more pervasive part of the purchase journey. While most research into online consumer behavior focuses on attitudes as an antecedent of product choice, this article focuses on an important but hardly explored variable that may be impacted by technology‐mediated environments: self‐accountability. Laboratory experiments suggest that self‐accountability may influence online purchases, but this has not been confirmed in field studies. Furthermore, although this prior work suggests that self‐accountability may impact product choice through the elicitation of guilt, the role of positive emotions has not been explored. Using two surveys with online retailers, this paper (a) shows that in a technology‐mediated environment, self‐accountability influences product choice; (b) proposes and confirms a complementary route for this effect through pride that is stronger than that through guilt; and (c) evidences the relationship between self‐accountability and perceived consumer effectiveness. These results show a clear opportunity for digital marketers to encourage self‐accountability, to thereby elicit pride and not just guilt, and hence to impact consumer decision making in technology‐mediated environments, particularly when choices have sustainability implications.